EVALUATION OF BORDER SECURITY OF STATES WITH A CYBER APPROACH - GÜLER, Ayşegül (Cyberpolitik Journal, 2019)
The internet has led to significant improvements in life as well as changes in threat detection. Developments in communication made state boundaries and national laws meaning less. The cyber attacks, which constitute a separate among the terrorist activities that have become wide spread today, have caused humanity to face a total attack that is not clear of its place and time. The internet allows people in remote are as to talk and communicate with each other by eliminating distances that cannot be expressed by classical concepts of time and space in seconds. It brings institutions and people together in the same field without the need for space. Information on the Internet, which allows people to announce their reactions instantly, is spreading unchecked, and the intervention may occur after the news is spread. As the virtual world rapidly surrounds life, its manager and owner are uncertain. The institutions created to manage themselves cannot keep up with the developments in terms of capacity. The rules that are tried to be created for the internet that develops without rules and without control become meaningless without being implemented. In the globalizing world, wide areas of freedom are opened to people, and no responsibility other than the will of the individual can be established for the protection of universal values. On the contrary, the institutions have prepared the basis for each individual to be vulnerable to a wide range of threats from health to economy, to basic human rights. At a time when states can not protect their information, the rights of persons are at a serious risk. There is no formula on the dimensions of the problems environment of uncertainty brought about by the change. There is an environment in which states are unprepared for cyber attacks, and even states that seem to be the center of technology cannot be protected from cyber attacks. Societies should be directed to global cooperation and rules should be established to ensure information security that will satisfy people with common reason rather than making profitable calculations out of chaos.